Conductive polymer coated lithium ion battery positive electrode material and preparation method thereof
Through conductive polymer coating technology, the structural stability and thermal stability of lithium-ion battery positive electrode materials in long-term circulation are solved, the cycle life and safety performance are improved, and more efficient battery performance and safety are achieved.
Patent Information
- Application Number
- CN202411635403.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-11-15
AI Technical Summary
The existing lithium-ion battery positive electrode materials have problems such as structural recombination, particle fragmentation, transition metal dissolution and poor thermal stability during long-term recycling, resulting in shortening of cycle life and safety hazards.
Using conductive polymer coating technology, the positive electrode material of lithium ion battery is formed by composite sintering of polyaniline-polyethylene glycol copolymer and nickel-cobalt lithium manganate lithium cobalt manganate to form a conductive polymer-coated lithium-ion battery to improve the structure of the material Stability and thermal stability reduce the risk of thermal runaway from the battery.
It significantly improves the cycle life and safety performance of lithium-ion batteries, enhances the thermal stability of the material, delays the battery's thermal runaway speed, and improves the cycle performance and safety performance of the battery at high voltages.
Smart Images

Figure CN119230737A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, in particular to a conductive polymer coated lithium ion battery positive electrode material and a preparation method thereof. Background Art
[0002] As the research on lithium-ion battery cathode materials continues to progress, in order to cater to the market demand for lithium nickel cobalt manganese oxide LiNi 1-x-y Co x Mn y In order to meet the high standards of energy density and safety performance of O2 materials, researchers have proposed a variety of innovative strategies. These strategies include: introducing new elements through doping or surface coating technology to optimize the electrochemical performance of materials, adjusting the ratio of metal elements to enhance battery capacity, and improving the morphology of materials to improve energy density. 1-x-y Co x Mn y In-depth research on O2 cathode materials has revealed the laws of their performance and structural changes. Studies have shown that high nickel content LiNi with layered structure 0.8 Co 0.1 Mn 0.1 O2 cathode material, due to its excellent specific capacity, outstanding cycle stability and economical cost-effectiveness, has gradually become one of the most promising cathode material options in commercial applications.
[0003] Nevertheless, although the high nickel content provides high energy density, it reduces the structural stability of the material and is prone to phase change and structural damage during charging and discharging. 0.8 Co 0.1 Mn 0.1 The surface chemical activity of O2 positive electrode material is high, and it is easy to react with electrolyte, resulting in capacity decay and shortened life. 0.8 Co 0.1 Mn 0.1 The thermal stability of O2 is relatively poor, which poses a safety hazard. As the number of cycles increases, LiNi 0.8 Co 0.1 Mn 0.1 O2 cathode materials will experience microcrack expansion and internal structure deterioration, affecting their cycle life.
[0004] In order to solve this dilemma, Chinese patent CN118619372A relates to a nickel-cobalt-manganese oxide material by constructing a zirconate and cerate composite coating structure, aiming to improve the initial discharge specific capacity, rate performance, cycle performance and high-temperature cycle stability of lithium-ion battery positive electrode materials. The patent effectively improves the electrochemical properties of the material by forming a composite coating layer on the surface of nickel-cobalt-manganese oxide. Patent CN118630169A describes a method for WC-W-2C heterostructure coating of conventional lithium-nickel-cobalt-manganese positive electrode materials, which can improve the rate performance of modified lithium-nickel-cobalt-manganese positive electrode materials, inhibit voltage decay, and provide excellent long-term cycle stability. Through this specific heterostructure coating, the electrochemical performance of the positive electrode material has been significantly improved. Patent CN114784248B This method forms a fast ion conductor layer on the surface of the ternary material through a dry acid-base reaction. The dry coating avoids the electrochemically inactive layer generated by the contact between the material and water in the wet coating, reduces the additional loss of lithium, and improves the material's cycle performance, rate performance and low temperature performance.
[0005] Although similar control methods can effectively improve the structural stability and cycle performance of nickel-cobalt-manganese-oxygen lithium-ion batteries, they are still far from the actual application requirements, and the process is cumbersome and costly. It is difficult for current positive electrode materials to balance the electrochemical properties such as manufacturing cost, capacity, internal resistance and their own safety. Therefore, there is an urgent need to develop a lithium-ion battery positive electrode material with good structural stability, excellent performance and high safety. Summary of the invention
[0006] The technical problem to be solved by the present invention is: in the prior art, a series of problems are often encountered in the long-term cyclic use of ternary positive electrode materials, such as structural reorganization, particle fragmentation, transition metal dissolution, and damage to the interface film between the positive electrode and the electrolyte; especially in the high-delithiation state, the thermal stability of the oxide positive electrode material is poor, and it is easy to decompose and release oxygen under high temperature conditions, causing a violent oxidation reaction of the electrolyte, generating a large amount of heat and gas, which may cause safety accidents such as battery fire or explosion in severe cases. In order to overcome the above shortcomings, the present invention provides a conductive polymer-coated lithium-ion battery positive electrode material and a preparation method thereof, which optimizes the production cost of the positive electrode material, enhances the stability of its crystal structure in a high voltage environment, reduces the side reactions on the interface, improves the thermal stability of the material, and reduces the risk of thermal runaway of the battery, thereby enhancing the cycle life and safety of the lithium-ion battery.
[0007] The technical solution adopted by the present invention to solve its technical problem is:
[0008] A conductive polymer coated lithium ion battery positive electrode material, comprising polyaniline (PANI)-polyethylene glycol (PEG) copolymer, nickel cobalt manganese oxide positive electrode material LiNi 1-x-y Cox Mn y O2 composite sintering; Among them, the positive electrode material LiNi 1-x-y Co x Mn y The mass percentage of O2 is 97-99.5%, and the balance is polyaniline-polyethylene glycol copolymer.
[0009] Furthermore, the polyaniline-polyethylene glycol copolymer is prepared by emulsion polymerization or solution polymerization.
[0010] Furthermore, the sintering method is a tubular furnace in an oxygen atmosphere or a muffle furnace in an air atmosphere.
[0011] Furthermore, the molecular weight of the polyethylene glycol in the polyaniline-polyethylene glycol copolymer is 200-400.
[0012] Furthermore, the lithium nickel cobalt manganese oxide positive electrode material LiNi 1-x-y Co x Mn y In O2, x is 0.05 to 0.2, and y is 0.05 to 0.3.
[0013] A method for preparing the above-mentioned conductive polymer coated lithium ion battery positive electrode material specifically comprises the following steps:
[0014] Step S1, weighing polyethylene glycol and aniline, mixing the two, adding deionized water, then adding dodecylbenzenesulfonic acid aqueous solution and ammonium peroxodisulfate, polymerizing at 0-5° C. for 6 hours, then washing in a centrifuge, and drying to obtain a polyaniline-polyethylene glycol copolymer;
[0015] Step S2, polyaniline-polyethylene glycol copolymer, lithium nickel cobalt manganese oxide positive electrode material LiNi 1-x-y Co x Mn y After O2 is mixed, anhydrous ethanol is added, and then placed in a mechanical mixing device for 1 hour, and mixed thoroughly to obtain a mixed powder;
[0016] Step S3, putting the mixed powder into a sample pool, and then placing it in a sintering furnace, sintering for 12 hours to obtain a primary product;
[0017] Step S4, putting the primary product into a mortar and grinding it to obtain a finished conductive polymer-coated lithium-ion battery positive electrode material.
[0018] Furthermore, in step S1, the mass ratio of polyethylene glycol to aniline is (4-8):1.86.
[0019] Furthermore, in step S2, the mixing temperature is 80°C.
[0020] Furthermore, in step S3, the sintering temperature is 400°C.
[0021] The beneficial effects of the present invention are as follows: the present invention has a reasonable design, a simple preparation method, and has the following advantages:
[0022] (1) The conductive polymer coated lithium ion battery positive electrode material of the present invention can significantly improve the cycle performance of nickel manganese oxide lithium ion batteries at high voltages between 2.8 and 4.4 V. Compared with existing positive electrode materials, the specific capacity of the battery is increased to 202.00 mA / g, and the capacity retention rate is increased to 75%;
[0023] (2) The conductive polymer coated lithium ion battery positive electrode material of the present invention can improve the thermal stability of the positive electrode material itself and increase the thermal decomposition reaction temperature of the positive electrode material, thereby slowing down the thermal runaway speed of the battery and improving the safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 A comparison diagram of cycle efficiency curves of half cells assembled in Examples 1 to 3 of the present invention and Comparative Example 1;
[0026] Figure 2 It is a comparison diagram of DSC curves of thermal analysis tests of the positive electrode materials in Examples 1 to 3 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0027] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0028] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this description, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] A conductive polymer coated lithium ion battery positive electrode material, comprising a copolymer polyaniline (PANI)-polyethylene glycol (PEG), a nickel cobalt manganese oxide positive electrode material LiNi 1-x-y Co x Mn y O2 composite sintering; Among them, the positive electrode material LiNi 1-x-y Co x Mn y The mass percentage of O2 is 97-99.5%, and the balance is polyaniline-polyethylene glycol copolymer.
[0031] The preparation method of the polyaniline-polyethylene glycol copolymer is emulsion polymerization or solution polymerization.
[0032] The sintering method is a tube furnace with oxygen atmosphere or a muffle furnace with air atmosphere.
[0033] The molecular weight of polyethylene glycol in the polyaniline-polyethylene glycol copolymer is 200-400.
[0034] LiNi Nickel Cobalt Manganese Oxide Cathode Material 1-x-y Co x Mn y In O2, x is 0.05 to 0.2, and y is 0.05 to 0.3.
[0035] A method for preparing the above conductive polymer coated lithium ion battery positive electrode material specifically comprises the following steps:
[0036] Step S1, weigh polyethylene glycol and aniline, mix the two, add deionized water, add dodecylbenzenesulfonic acid aqueous solution and ammonium peroxodisulfate, polymerize at 0-5°C for 6h, wash in a centrifuge, and dry at 80°C to obtain a polyaniline-polyethylene glycol copolymer;
[0037] Step S2, polyaniline-polyethylene glycol copolymer, lithium nickel cobalt manganese oxide positive electrode material LiNi 1-x-y Co x Mn y After mixing with O2, add 100 ml of anhydrous ethanol, and then put it into a mechanical mixing device. The mixing time is 1 hour and the mixing temperature is 80°C. After fully mixing, a mixed powder is obtained;
[0038] Step S3, putting the mixed powder into a sample pool, and then placing it in a sintering furnace at a sintering temperature of 400° C. for 12 hours to obtain a primary product;
[0039] Step S4, putting the primary product into a mortar and grinding it for 5 minutes to obtain a finished conductive polymer-coated lithium-ion battery positive electrode material.
[0040] Example 1
[0041] A method for preparing a conductive polymer coated lithium ion battery positive electrode material, specifically comprising the following steps:
[0042] Step S1, weighing 6 g of polyethylene glycol and 1.86 g of aniline, adding 60 ml of deionized water, adding an aqueous solution of dodecylbenzenesulfonic acid and ammonium peroxodisulfate, polymerizing at 5° C. for 6 h, then washing in a centrifuge, and drying at 80° C. to obtain a polyaniline-polyethylene glycol copolymer; the molecular weight of the polyaniline-polyethylene glycol copolymer is 300;
[0043] Step S2: 0.02 g of polyaniline-polyethylene glycol copolymer and 1.98 g of lithium nickel cobalt manganese oxide positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 After mixing with O2, add 100 ml of anhydrous ethanol, and then put it into a mechanical mixing device. The mixing time is 1 hour and the mixing temperature is 80°C. After fully mixing, a mixed powder is obtained;
[0044] Step S3, putting the mixed powder into a sample pool, and then placing it in a tube furnace in an oxygen atmosphere, sintering at a temperature of 400° C. for 12 hours to obtain a primary product;
[0045] Step S4, putting the primary product into a mortar and grinding it for 5 minutes to obtain a finished conductive polymer-coated lithium-ion battery positive electrode material.
[0046] A manufacturing process of a positive electrode sheet is as follows: a conductive polymer-coated lithium-ion battery positive electrode material, a conductive agent acetylene black, and a binder polyvinylidene fluoride (PVDF) are mixed according to a mass ratio of positive electrode material: acetylene black: polyvinylidene fluoride = 8:1:1, and after the mixing is completed, N-methylpyrrolidone (NMP) is added, and the mixture is fully stirred to form a uniform positive electrode slurry and evenly coated on a 15μm thick aluminum foil, and then dried at 120°C in a forced air drying oven for 12 hours to obtain a positive electrode sheet for use.
[0047] The manufacturing process of a positive electrode half-cell is as follows: the above-mentioned positive electrode sheet is used as the positive electrode, the metal lithium sheet is used as the negative electrode, Celgard 2500 is used as the separator, an electrolyte is added, and a button-type half-cell with a battery model of CR2032 is assembled in a glove box.
[0048] The battery cycle test steps are as follows:
[0049] The assembled button half-cell was left at room temperature (25°C) for 12 h and then cycled, with a charge and discharge voltage of 2.8 to 4.4 V. The button half-cell was first charged and discharged for three cycles at a current of C / 10, and then for 50 to 100 cycles at a current of C / 5.
[0050] The test procedure is: C / 20 constant current charging to 4.4V, and then C / 20 discharge to 2.8V. After fully activating the electrode material, the battery is charged and discharged for 100 cycles at C / 5 to evaluate the cycle stability.
[0051] The thermal analysis test process is as follows:
[0052] After the cycle is completed, the button half-cell is disassembled in the glove box, the positive electrode sheet is separated, and the positive electrode sheet is cleaned with dimethyl carbonate solvent to remove the residual electrolyte and left to dry. The electrode material is scraped off the aluminum sheet, and 5 mg ± 0.5 mg of the electrode sheet is weighed and placed in the sample cell. The differential scanning calorimeter DSC experiment is carried out on the thermal analyzer with a heating range of 100-400 ° C and a heating rate of 10.0 ° C / min. Conductive polymer coated lithium ion battery. As a comparison, DSC experiments are carried out separately on samples of different positive electrode materials.
[0053] Example 2
[0054] The difference from Example 1 is that: in step S1 of this embodiment, 4 g of polyethylene glycol and 1.86 g of aniline are weighed and mixed, 60 ml of deionized water is added, and then an aqueous solution of dodecylbenzenesulfonic acid and ammonium peroxydisulfate are added, polymerized at 5° C. for 6 h, then centrifuged and washed, and dried at 80° C. to obtain a polyaniline-polyethylene glycol copolymer; the molecular weight of the polyaniline-polyethylene glycol copolymer is 200.
[0055] The positive electrode material and button-type half-cell were prepared in the same manner as in Example 1, and the cycle performance and thermal analysis tests were performed.
[0056] Example 3
[0057] The difference from Example 1 is that: in step S1 of this embodiment, 8 g of polyethylene glycol and 1.86 g of aniline are weighed and mixed, 60 ml of deionized water is added, and then an aqueous solution of dodecylbenzenesulfonic acid and ammonium peroxydisulfate are added, polymerized at 5° C. for 6 h, then centrifuged and washed, and dried at 80° C. to obtain a polyaniline-polyethylene glycol copolymer; the molecular weight of the polyaniline-polyethylene glycol copolymer is 400.
[0058] The positive electrode material and button-type half-cell were prepared in the same manner as in Example 1, and thermal analysis tests were performed.
[0059] Comparative Example 1
[0060] The difference from Example 1 is that the positive electrode material of the battery in this comparative example is a ternary positive electrode material in the prior art.
[0061] The positive electrode material and positive electrode half-cell were prepared in the same manner as in Example 1, and the cycle performance and thermal stability tests were performed.
[0062] from Figure 1 It can be seen that compared with Examples 1 to 3, when the molecular weight of ethylene glycol is adjusted to 300, the cycle performance of the battery is significantly improved. The cycle performance results of the three button half-cells show that the reversible capacity of the three positive electrode materials increases in a gradient, and after long-term cycling, the capacity of Examples 1 to 3 and Comparative Example 1 decreases by 33%, 35%, 38% and 42%, respectively. It can be seen that Example 1 has a greater advantage in cycle stability.
[0063] Thermal safety performance: Figure 2 The DSC test results in the table show that the conductive polymer coated lithium ion battery positive electrode materials corresponding to Example 1 all exhibit good thermal stability. The initial exothermic temperatures of Examples 1 to 3 are all later than those of Comparative Example 1, and the initial exothermic temperature of Example 2 is delayed by 25°C compared with Comparative Example 1. Figure 2 As shown, the heat release of Example 1, Example 2, and Example 3 is significantly lower than that of Comparative Example 1. By calculation, it can be obtained that the heat release of Example 3 is 138.42 J, and the heat release of Comparative Example 1 is 212.28 J. Therefore, the positive electrode material coated with a conductive polymer prepared by the present invention can maximize the stability of the material, thereby reducing the heat generation of the positive electrode material and effectively inhibiting the initiation reaction of thermal runaway of the battery.
[0064] In summary, the conductive polymer-coated lithium-ion battery positive electrode material described in the present invention effectively improves the migration rate of lithium ions inside the positive electrode material and prevents the structural degradation of the material during the cycle process, thereby enhancing the cycle stability of the battery in a high voltage environment, and also ensures that the lithium-ion battery has excellent safety performance while maintaining high voltage cycle characteristics.
[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A conductive polymer coated lithium ion battery positive electrode material, characterized in that: The conductive polymer coated lithium ion battery positive electrode material is composed of polyaniline-polyethylene glycol copolymer, nickel cobalt manganese oxide lithium positive electrode material LiNi 1-x-y Co x Mn y O2 composite sintering; Among them, the positive electrode material LiNi 1-x-y Co x Mn y The mass percentage of O2 is 97-99.5%, and the balance is polyaniline-polyethylene glycol copolymer.
2. The conductive polymer coated lithium ion battery positive electrode material according to claim 1, characterized in that: The preparation method of the polyaniline-polyethylene glycol copolymer is an emulsion polymerization method or a solution polymerization method.
3. The conductive polymer coated lithium ion battery positive electrode material according to claim 1, characterized in that: The sintering method is a tubular furnace in an oxygen atmosphere or a muffle furnace in an air atmosphere.
4. The conductive polymer coated lithium ion battery positive electrode material according to claim 1, characterized in that: The molecular weight of the polyethylene glycol in the polyaniline-polyethylene glycol copolymer is 200-400.
5. The conductive polymer coated lithium ion battery positive electrode material according to claim 1, characterized in that: The lithium nickel cobalt manganese oxide positive electrode material LiNi 1-x-y Co x Mn y In O2, x is 0.05 to 0.2, and y is 0.05 to 0.
3.
6. A method for preparing a conductive polymer coated lithium ion battery positive electrode material as claimed in any one of claims 1 to 5, characterized in that: The specific steps include: Step S1, weighing polyethylene glycol and aniline, mixing the two, adding deionized water, then adding dodecylbenzenesulfonic acid aqueous solution and ammonium peroxodisulfate, polymerizing at 0-5° C. for 6 hours, then washing in a centrifuge, and drying to obtain a polyaniline-polyethylene glycol copolymer; Step S2, weighing polyaniline-polyethylene glycol copolymer, lithium nickel cobalt manganese oxide positive electrode material LiNi 1-x-y Co x Mn y O2, after the two are mixed, anhydrous ethanol is added, and then placed in a mechanical mixing device for 1 hour, and mixed thoroughly to obtain a mixed powder; Step S3, putting the mixed powder into a sample pool, and then placing it in a sintering furnace, sintering for 12 hours to obtain a primary product; Step S4, putting the primary product into a mortar and grinding it to obtain a finished conductive polymer-coated lithium-ion battery positive electrode material.
7. The method for preparing a conductive polymer-coated lithium-ion battery positive electrode material according to claim 6, characterized in that: In the step S1, the mass ratio of polyethylene glycol to aniline is (4-8):1.
86.
8. The method for preparing a conductive polymer coated lithium ion battery positive electrode material according to claim 6, characterized in that: In the step S2, the mixing temperature is 80°C.
9. The method for preparing a conductive polymer-coated lithium-ion battery positive electrode material according to claim 6, characterized in that: In the step S3, the sintering temperature is 400°C.
Citation Information
Patent Citations
Coated modified high nickel ternary positive electrode material, preparation method thereof and lithium ion battery
CN114784248B
Composite coated positive electrode material as well as preparation method and application thereof
CN118619372A
Positive electrode material containing heterojunction coating layer as well as preparation method and application of positive electrode material
CN118630169A
Preparation method of fast ion conductor and conducting polymer dual-modified ternary cathode material for lithium-ion battery
CN107706390A
Polyaniline / polyethylene glycol-co-coated composite ternary positive electrode material and preparation and application thereof
CN108711613A
